Dorsal-Ventral Gene Expression in the Drosophila Embryo Reflects the Dynamics and Precision of the Dorsal Nuclear Gradient - Reeves, Gregory T. (2012)
Patterning of the dorsal-ventral axis in the early Drosophila embryo depends on the nuclear distribution of the Dorsal transcription factor. Using live two-photon light-sheet microscopy, we quantified the nuclear Dorsal gradient in space and time and found that its amplitude and basal levels display oscillations throughout early embryonic development. These dynamics raise questions regarding how cells can reproducibly establish patterns of gene expression from a rapidly varying signal. We therefore quantified domains of Dorsal target genes, discovering their expression patterns are also dynamic. Computational modeling of this system reveals a correlation between Dorsal gradient dynamics and changes in target gene expression and suggests that these dynamics, together with time averaging of noise, results in the formation of graded gene expression borders in regions where the gradient is nearly flat. We propose that mRNA levels remain plastic during transient signaling events, allowing tissues to refine patterns in the face of genetic or environmental variation.